(Board)ing Schools: Rudyard Kipling’s young heroes - Rodrigues, Patricia (2019)
Rudyard Kipling’s young male characters, namely Stalky (Stalky & Co. ) and Harvey Cheyne Junior (Captains Courageous), whom he portrays with noticeable admiration, exhibit, on the one hand, circumspection, stoicism, leadership, and stalkiness, on the other hand, the absence of scruples in manipulating those acting in loco parentis to achieve their desired ends. This article aims to examine how these characters can shed light on one another, allowing for a better comprehension of them both. Furthermore, it will explore how the religious archetype of the trinity permeates Stalky & Co.’s composition of characters, and how muscular Christianity shapes Captains Courageous. Stalky and Harvey thrive in a masculine world, access to which requires leaving women behind, substituting them with brotherhoods or identification with the father. The perfect man, Kipling postulates, is the resourceful and courageous rule-bending Christian who is able to keep women and natives in a state of obedience.